2016
DOI: 10.1371/journal.pone.0151758
|View full text |Cite
|
Sign up to set email alerts
|

PLAG (1-Palmitoyl-2-Linoleoyl-3-Acetyl-rac-Glycerol) Modulates Eosinophil Chemotaxis by Regulating CCL26 Expression from Epithelial Cells

Abstract: Increased number of eosinophils in the circulation and sputum is associated with the severity of asthma. The respiratory epithelium produces chemokine (C-C motif) ligands (CCL) which recruits and activates eosinophils. A chemically synthesized monoacetyl-diglyceride, PLAG (1-palmitoyl-2-linoleoyl-3-acetyl-rac-glycerol) is a major constituent in the antlers of Sika deer (Cervus nippon Temminck) which has been used in oriental medicine. This study was aimed to investigate the molecular mechanism of PLAG effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Tregs have two primary functions, immune response and immunosuppression; they can secrete a variety of anti-inflammatory cytokines and play a key role in inflammation inhibition in immune regulation (8,24). At present, CCL26 is the most selective and active chemotactic agent, which is mainly expressed on the surface of eosinophils, mast cells and Th2 lymphocytes (25). In certain inflammation processes, CCL26 can even promote eosinophil chemotaxis and the recruitment to the inflammatory foci, further promoting degranulation and releasing eosinophil cationic proteins, as well as other cytotoxic substances, which in turn causes a series of inflammatory cascades and finally results in inflammatory damage to brain tissues (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Tregs have two primary functions, immune response and immunosuppression; they can secrete a variety of anti-inflammatory cytokines and play a key role in inflammation inhibition in immune regulation (8,24). At present, CCL26 is the most selective and active chemotactic agent, which is mainly expressed on the surface of eosinophils, mast cells and Th2 lymphocytes (25). In certain inflammation processes, CCL26 can even promote eosinophil chemotaxis and the recruitment to the inflammatory foci, further promoting degranulation and releasing eosinophil cationic proteins, as well as other cytotoxic substances, which in turn causes a series of inflammatory cascades and finally results in inflammatory damage to brain tissues (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…As reported elsewhere, it has been shown that PLAG is an effective therapeutic candidate in different inflammatoryassociated diseases, such as rheumatoid arthritis, atopic dermatitis, asthma and hepatitis (20,(34)(35)(36). In addition, the therapeutic efficacy of PLAG has been demonstrated in chemotherapy and radiation-induced oral mucositis in hamster and mouse models, through the effective attenuation of neutrophil infiltration into cheek pouches and tongues and a decrease in inflammatory cytokines (37).…”
Section: Discussionmentioning
confidence: 70%
“…The chemically synthesized lipid molecule, 1-palmitoyl-2linoleoyl-3-acetyl-rac-glycerol (PLAG), also known as EC-18, is identical to a major constituent found in the antlers of sika deer (19,20). Previously, the therapeutic efficacy of PLAG has been demonstrated in chemotherapy-associated hematopoietic dysfunction (21).…”
Section: Introductionmentioning
confidence: 99%
“…S1B). Migration assay was performed as described previously with minor modifications [24]. Briefly, THP-1 cells were pretreated with various concentrations of PLAG for 1 h and stimulated with gemcitabine for 24 h. The THP-1 supernatant was placed on the bottom chamber as chemoattractant.…”
Section: Methodsmentioning
confidence: 99%